Impact of demographic factors and HIV status on Hepatitis B vaccination adherence and completion rate among high-risk populations in Lagos State, Nigeria - Elizabeth Shoyemi; Ojore Godday Aghedo; Collins Obi; Chukwuebuka Peter Kelvin Uwaoma; Oluwafisayomi S. Azeez; Okikiola Oyeniyi (PLoS ONE, 2026)
Hepatitis-B-Virus (HBV) remains an important global public health concern, as well as a primary cause of both acute and chronic liver diseases, with over 18 million people infected by the virus in Nigeria. This study evaluated the impact of HIV status, age, and gender of high-risk populations on HBV vaccination adherence and completion rate in Lagos state, Nigeria. A retrospective study design was utilized to access the clinic data of 641 study participants who participated in the HBV program at the one-stop-shop clinic between June 2021 to June 2024. Data on age, HIV status, gender, population type, and the date of each dose of administered vaccine were recorded. To estimate the odds-ratios (ORs) and adjusted-ORs at 95% confidence intervals (CIs), bivariate/multivariate logistic regression models were utilized, and the association between age, gender, HIV status, and HBV vaccination adherence and the completion rate was examined. The study participants had a mean age of 21.7 ± 8.8 years and were composed of 510 (79.6%) males, 131 (20.4%) females; 162 (25.3%) participants living with HIV, 423 (66.0%) HIV-negative participants, 500 (78.0%) MSM, and 115 (17.9%) FSW. The overall vaccination completion rate was 45.4%, with significant variation by age group (p = 0.004). The highest completion rates were observed among participants aged 30–34 years (58.4%) and 35–39 years (57.8%), while younger participants aged 15–29 had lower adherence. Gender and HIV status were not independently associated with vaccination completion (p > 0.05). Age was the only factor significantly affecting completion (AOR: 1.92, 95% CI: 1.23, 3.03). HBV vaccination coverage in high-risk populations is low in Lagos State. This suggests that the HBV vaccination program in the state is still facing significant challenges. Creating awareness about HBV infection and strengthening the availability, accessibility, and cost effectiveness of HBV service uptake will enhance the program's success.